Callus Initiation and Plant Regeneration of Caladium Bicolor (AITON) Vent: By in Vitro C ulture - Sakpere, A. M. A.; Adebona, A. C. (2014)
A method for the direct plant regeneration of Caladium bicolor (Aiton) Vent is described. Callus was induced from corm and leaf explants of C. bicolor on Murashige and Skoog (MS) medium supplemented with 0.8 mg/L2, 4-Dichlorophenoxyacetic acid (2,4-D) in combination with 1mg/l kinetin. The callus which was white arid compact was scanty and shortlived. Rootlets and shootlets were generated on corm explants inoculated on medium supplemented with kinetin and NAA as well as various concentrations of 2,4-D. Corm and leaf explants had a 50 % response each to all the concentrations of 2.4-D used. More callus was induced from leaf explants than from petiole or corm explants.